1998
DOI: 10.1111/j.1750-3639.1998.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

Glial‐Neuronal Interactions in Alzheimer's Disease: The Potential Role of a ‘Cytokine Cycle’ in Disease Progression

Abstract: The role of glial inflammatory processes in Alzheimer's disease has been highlighted by recent epidemiological work establishing head trauma as an important risk factor, and the use of anti-inflammatory agents as an important ameliorating factor, in this disease. This review advances the hypothesis that chronic activation of glial inflammatory processes, arising from genetic or environmental insults to neurons and accompanied by chronic elaboration of neuroactive glia-derived cytokines and other proteins, sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
314
2
13

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 656 publications
(334 citation statements)
references
References 66 publications
5
314
2
13
Order By: Relevance
“…In the brains of both AD individuals and transgenic animal models, it was found that Ab plaques are surrounded by activated glial cells (Bauer et al 1991;Cagnin et al 2001;Fillit et al 1991;Liu et al 2013;Varnum and Ikezu 2012). Activated microglia and astrocytes strongly secrete inflammatory components such as pro-inflammatory cytokines, chemokines, complement, macrophage inflammatory proteins, monocyte chemoattractant proteins, reactive oxygen species (ROS), nitric oxide (NO) prostaglandins, leukotrienes, thromboxanes and so on (Akiyama et al 2000;Griffin et al 1998;Mrak et al 1995;Town et al 2005;Tuppo and Arias 2005). The released inflammatory molecules, especially some cytokines such as interleukin (IL)-18, IL-1b and tumor necrosis factor (TNF)-a, impair the balance of normal neurophysiologic condition that correlates with cognition and learning and memory (Fillit et al 1991;Gemma and Bickford 2007;Jankowsky and Patterson 1999;Liu et al 2013;Varnum and Ikezu 2012).…”
Section: Inflammation In Admentioning
confidence: 99%
“…In the brains of both AD individuals and transgenic animal models, it was found that Ab plaques are surrounded by activated glial cells (Bauer et al 1991;Cagnin et al 2001;Fillit et al 1991;Liu et al 2013;Varnum and Ikezu 2012). Activated microglia and astrocytes strongly secrete inflammatory components such as pro-inflammatory cytokines, chemokines, complement, macrophage inflammatory proteins, monocyte chemoattractant proteins, reactive oxygen species (ROS), nitric oxide (NO) prostaglandins, leukotrienes, thromboxanes and so on (Akiyama et al 2000;Griffin et al 1998;Mrak et al 1995;Town et al 2005;Tuppo and Arias 2005). The released inflammatory molecules, especially some cytokines such as interleukin (IL)-18, IL-1b and tumor necrosis factor (TNF)-a, impair the balance of normal neurophysiologic condition that correlates with cognition and learning and memory (Fillit et al 1991;Gemma and Bickford 2007;Jankowsky and Patterson 1999;Liu et al 2013;Varnum and Ikezu 2012).…”
Section: Inflammation In Admentioning
confidence: 99%
“…Evidence indicates that astrocytes beneficially contribute to clearance of accumulated Aβ [109,110], but also contribute to inflammatoryinduced neuronal damage such as by producing neurotoxic nitric oxide [111] and cytokines. Activated microglia also release inflammatory cytokines and nitric oxide, as well as reactive oxygen species, and activate the complement system [112]. Thus, on one hand, these inflammatory molecules produced by glia cells are thought to contribute to the pathological progression of AD, while on the other hand, by contributing to the clearance of Aβ and secreting growth factors, both activated astrocytes and microglia are not thought to be entirely detrimental in AD [113,114].…”
Section: Neurodegenerative Diseases: Gsk3 and Admentioning
confidence: 99%
“…inflammatory response in the brain that exceeds early neuroprotection and results in neurodegenerative changes capable of continuing the inflammatory cycle. 9,27,90 Chronic inflammation has been observed in a number of studies examining patients with trauma-related anxiety disorders, reporting increases in downstream mediators, such as peripheral elevations of TNF-a, interferon-gamma (IFN-c), IL-1b, and IL-6, in patients with PTSD, [13][14][15][16] elevations of TNF-a and IL-6 in patients with OCD, 17 and elevations in proinflammatory cytokines and chemokines (monocyte chemoattractant protein 1, macrophage inflammatory protein 1 alpha, IL-1a, IL-1b, IL-6, IL-8, Eotaxin, granulocyte macrophage colony-stimulating factor, and IFN-c) in individuals with panic disorder and PTSD. 18 Despite compelling evidence implicating excessive inflammatory actions and a generalized inflammatory state in the development of anxiety disorders after TBI, central measures of proinflammatory cytokine elevations specifically related to human PTSD and other anxiety disorders have not yet been performed.…”
mentioning
confidence: 99%